Ranking Fuzzy Cognitive Map based scenarios using ELECTRE III: Applied on housing market. Issue 5 (17th June 2016) - Shafia, Mohammad Ali; Rahimi Moghaddam, Mohammad; Teimoury, Ebrahim
Abstract: Policy makers often deal with a wide range of alternative probable future states for the entity they work for – a country, for example. To strive for the most desirable state, the policy makers must evaluate and rank all probable future scenarios. To this end, 'scenario methods' gained recent popularity are increasingly being employed. Nevertheless, currently, decisions made based on insight gained from scenarios are not made in an integrated systematic process. Current variants of the method help study the role of any research concept individually; thus, they do not provide a complete picture of the research situation. A more suitable variant of the method for today's world should provide a holistic view of the research situation by modelling possible links among research concepts. This paper, introduces a stepwise methodology that can guide the building, developing, and ranking of possible future scenarios, having factored in the possible causal interrelations among research concepts. The method is enriched with a combination of Fuzzy Cognitive Maps, a widely used soft computing method, and ELECTRE III, a popular method of Multi Attribute Decision Making. This paper also presents the results of the application of the proposed methodology for Iran's housing market, highlighting the advantages of the proposed methodology.